Global Climate Risk Index and Firm Performance: Evidence from Turkish Firms - (:unkn) unknown (Springer Nature, 2021)
Climate change, which currently has a multidimensional effect on many factors such as national economies and firms, will continue to be the most substantial global risk in the next decade according to the World Economic Forum’s 2020 Global Risks Report. Although firms strive to reduce the risk of climate change with various tools, it continues to affect firms’ performance. Therefore, the impact of climate change risk on governance, accounting, and finance is being frequently discussed in recent years. In this study, the impact of the Global Climate Risk Index (CRI)—compiled and published by Germanwatch (Kreft and Eckstein 2014)—on firm performances is analyzed. 167 manufacturing firms listed in Borsa Istanbul (BIST) are considered. The time span for the study is between 2006 and 2018. All data are obtained from Thomson Reuters Datastream and Thomson Reuters Eikon. The panel fixed effect model is used for the analysis. The results of the study indicate that there is a negative and significant relationship between Return on Assets (ROA) and CRI. In addition, firms reduce their total debt when CRI increases. Finally, when the CRI increases, the tendency of firms to pay dividends declines and their cash holding tendency increases. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.
Keywords: Climate change; Climate risk; Firm performance; Global climate risk index; Panel fixed effects